Intimate Partner Violence against Women: Practice and Attitude in South Wollo and East Gojjam Zones of Amhara National Regional State - Abebe, Mulunesh; Asres, Kerebih (Ethiopian Journal of Social Sciences, 2015)
Intimate partner violence against women (IPV) is a critical social problem in developing countries like Ethiopia. However, little research has been done to investigate the extent of the problem and the society’s attitude in South Wollo and East Gojjam Zones of Amhara Region. This study investigates women’s decision making participation in household matters, physical and sexual abuse, and attitude towards wife beating using both quantitative and qualitative methods. The findings show that women are deprived of their decision making rights, physical and sexual abuse of women are highly prevalent and are considered as ‘normal’ part of marital relationship. Majority of participants (66 %) support wife beating and statistically significant higher proportion of women support wife beating than their male counterparts. The findings indicate that women are experiencing high levels of intimate partner violence in the domestic sphere. Therefore, this issue should be a critical concern for social workers, other professionals and policy makers.